Factors that Contribute to the Fatigue of Midwives and Nurses in the Patient Installation of Solok Selatan Hospital - Asep Irfan; Ghali Sabawi Maruf; Basuki Ario Seno (Miracle Journal Get Press, 2024)
According to the World Health Organization (WHO), severe fatigue will become the second killer disease after heart disease. In 2021, there were 31,801 cases of work accidents, an increase of 16.96% from the previous year, according to the BPJS Employment of West Sumatra Region. The purpose of this study was to determine the factors that contribute to nurse and midwife fatigue in the Inpatient Installation of South Solok Hospital. This study used an analytic cross-sectional survey approach with a sample of 84 people. Data were obtained through questionnaire sheets and direct observation. Data were processed using a computer, and the results were displayed in the form of frequency distribution tables. The results showed that the p value of workload (0.05 = α with OR = 2.625), work climate (0.003 < α with OR = 4.278), work stress (0.001 < α with OR = 5.600), and fatigue work tired 59.5%, heavy workload 60.7%, and long service 53.6%. Thus, it can be concluded that there is a significant relationship between workload and work climate. It is hoped that maintaining a balance between personal life and work is the key to overcoming work fatigue. To stay healthy in the long run, try to lead a regular and healthy lifestyle.